United States energy and CO2 savings potential from deployment of near-infrared electrochromic window glazings. (July 2015) - DeForest, Nicholas; Shehabi, Arman; O'Donnell, James; Garcia, Guillermo; Greenblatt, Jeffery; Lee, Eleanor S.; Selkowitz, Stephen; Milliron, Delia J.
Abstract: This paper presents a simulation study of the energy and CO2 benefits of a transparent, near-infrared switching electrochromic (NEC) glazing for building applications. NEC glazings are an emerging dynamic window technology that can modulate the transmission of NIR heat without affecting transmission of visible light. In this study, a hypothetical NEC glazing is simulated on clear and tinted glass in six building type models in 16 U.S. climate regions using Energy Plus 7.1. The total annual energy consumption for lighting, heating, cooling, and ventilation for the NEC glazings are compared with high performance static windows and conventional tungsten-oxide EC glazings. Using regional CO2 intensities and building stock totals, the results from individual building model simulations are scaled up to national totals. The U.S. national savings from NEC deployment is found to be 167 TWh/yr (600 PJ/yr) compared to the existing building stock, but only 8 TWh/yr (29 PJ/yr) or 1.56 million tonnes of CO2 per year when compared to high performance static glazings with lighting controls installed. NEC performance varied significantly by building type and location. This analysis reveals that 50% of the total energy savings can be realized by deploying NEC glazings in only 18% of the total window stock, and 75% of the savings in only 39% of the stock. The best performing locations include medium offices and midrise residential buildings in northern climates, where energy savings per unit window area range from 50 to 200 kWh/m 2 -yr. Highlights: We model a transparent electrochromic window glazing in six building types. Simulations are conducted for 16 cities to determine energy and carbon savings. Transparent electrochromic glazings outperform alternatives in Northern climates. The best regions see 3%–9% savings for heating, cooling, and lighting consumption. Full U.S. deployment saves 8 TWh primary energy and 1.56 billion kg CO2 per year.